237. A Case-Control Study Investigating Household, Community, and Clinical Risk Factors Associated with Multisystem Inflammatory Syndrome in Children (MIS-C) after SARS-CoV-2 Infection. (15th December 2022) - Zambrano, Laura D; Wu, Michael J; Martin, Lora M; Malloch, Lacy; Newhams, Margaret M; Son, Mary Beth; Sanders, Cameron; Patterson, Kayla; Halasa, Natasha B; Fitzgerald, Julie C; Leroue, Matthew; Hall, Mark; et al.
Abstract: Background: Risk factors for MIS-C, a rare but serious hyperinflammatory syndrome associated with SARS-CoV-2 infection, remain unclear. We evaluated household, clinical, and environmental risk factors potentially associated with MIS-C. Methods: This investigation included MIS-C cases hospitalized in 14 US pediatric hospitals in 2021. Outpatient controls were frequency-matched to case-patients by age group and site and had a positive SARS-CoV-2 viral test within 3 months of the admission of their matched MIS-C case (Figure 1). We conducted telephone surveys with caregivers and evaluated potential risk factors using mixed effects multivariable logistic regression, including site as a random effect. We queried regarding exposures within the month before hospitalization for MIS-C cases or the month after a positive COVID-19 test for controls. Figure. Patient enrollment timeline. Enrollment scheme for MIS-C case-patients and SARS-CoV-2-positive outpatient controls. MIS-C case-patients were identified through hospital electronic medical records, while two outpatient controls per case were identified through registries of outpatient SARS-CoV-2 testing logs at facilities affiliated with that medical center. Caregivers of outpatient controls were interviewed at least four weeks after their positive test to ensure they did not develop MIS-C after their infection. Results: We compared 275 MIS-C case-patients with 494 outpatient SARS-CoV-2-positive controls. Race, ethnicity and social vulnerability indices were similar. MIS-C was more likely among persons who resided in households with >1 resident per room (aOR=1.6, 95% CI: 1.1–2.2), attended a large (≥10 people) event with little to no mask-wearing (aOR=2.2, 95% CI: 1.4–3.5), used public transportation (aOR=1.6, 95% CI: 1.2–2.1), attended school >2 days per week with little to no mask wearing (aOR=2.1, 95% CI: 1.0–4.4), or had a household member test positive for COVID-19 (aOR=2.1, 95% CI: 1.3–3.3). MIS-C was less likely among children with comorbidities (aOR=0.5, 95% CI: 0.3–0.9) and in those who had >1 positive SARS-CoV-2 test at least 1 month apart (aOR=0.4, 95% CI: 0.2–0.6). MIS-C was not associated with a medical history of recurrent infections or family history of underlying rheumatologic disease. Conclusion: Household crowding, limited masking at large indoor events or schools and use of public transportation were associated with increased likelihood of developing MIS-C after SARS-CoV-2 infection. In contrast, decreased likelihood of MIS-C was associated with having >1 SARS-CoV-2 positive test separated by at least a month. Our data suggest that additional studies are needed to determine if viral load, and/or recurrent infections in the month prior to MIS-C contribute to MIS-C risk. Medical and family history were not associated with MIS-C in our analysis. Disclosures: Natasha B. Halasa, MD, Quidel: Grant/Research Support|Quidel: equipment donation|Sanofi: Grant/Research Support|Sanofi: HAI testing and vaccine donation Mark Hall, MD, Abbvie: Service on a Data Safety Monitoring Board|Kiadis: Licensing income unrelated to the current submission Mary A. Staat, MD, MPH, Centers for Disease Control and Prevention: Grant/Research Support|Cepheid: Grant/Research Support|National Institute of Health: Grant/Research Support|Uptodate: Royalties Pia S. Pannaraj, MD, MPH, AstraZeneca: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi-Pasteur: Advisor/Consultant|Seqirus: Advisor/Consultant Charlotte V. Hobbs, MD, Biofire (Biomerieux): Advisor/Consultant.